2022
DOI: 10.3390/mi13040574
|View full text |Cite
|
Sign up to set email alerts
|

Electrografting a Hybrid Bilayer Membrane via Diazonium Chemistry for Electrochemical Impedance Spectroscopy of Amyloid-β Aggregation

Abstract: Herein, a novel hybrid bilayer membrane is introduced as a platform to study the aggregation of amyloid-β1–42 (Aβ1–42) peptide on surfaces. The first layer was covalently attached to a glassy carbon electrode (GCE) via diazonium electrodeposition, which provided a highly stable template for the hybrid bilayer formation. To prepare the long-chain hybrid bilayer membrane (lcHBLM)-modified electrodes, GCE surfaces were modified with 4-dodecylbenzenediazonium (DDAN) followed by the modification with dihexadecyl ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…It is well-known that UV-Vis SEC has been applied in many fields, for example, in electron transfer processes [ 55 ], solar cells [ 31 , 56 ], memory devices [ 57 ], and the determination of compounds of biological interest [ 10 , 58 , 59 , 60 ]. A detailed summary of the chosen examples’ electrode configurations and light arrangements is given in Table 2 .…”
Section: Ultraviolet-visible Sec (Uv-vis Sec)mentioning
confidence: 99%
See 2 more Smart Citations
“…It is well-known that UV-Vis SEC has been applied in many fields, for example, in electron transfer processes [ 55 ], solar cells [ 31 , 56 ], memory devices [ 57 ], and the determination of compounds of biological interest [ 10 , 58 , 59 , 60 ]. A detailed summary of the chosen examples’ electrode configurations and light arrangements is given in Table 2 .…”
Section: Ultraviolet-visible Sec (Uv-vis Sec)mentioning
confidence: 99%
“…The combination of SERS with electrochemistry has emerged as a powerful tool to monitor the structural changes of surface adsorbates [ 95 , 96 ], reaction intermediates [ 97 , 98 ], and quantitative analysis of electrolysis products [ 24 , 60 ]. Daniel and co-workers showed that the SERS SEC technique achieved a theoretical ferricyanide detection limit (~1.5 × 10 −8 M) in a 0.1 M KCl solution [ 24 ].…”
Section: Surface-enhanced Raman Spectroscopy Sec (Sers Sec)mentioning
confidence: 99%
See 1 more Smart Citation